GCT-11. 24 Gy whole ventricular radiotherapy alone is sufficient for disease control in localised germinoma in CR after initial chemotherapy – final of the SIOP CNS GCT II study. (3rd June 2022) - Calaminus, Gabriele; Bison, Brigitte; Conter, Cecile Faure; Frappaz, Didier; Peyrl, Andreas; Gerber, Nicolas U; Müller, Jans-Enno; Ajithkumar, Thankamma; Morana, Giovanni; Cross, Justin; Pietsch, Torsten; Smith, Colin; et al.
Abstract: SIOP CNS GCT II aimed to establish if 24 Gy Whole Ventricular Radiotherapy (WVRT) in localised germinoma is sufficient for tumour control. After central review of radiological response after 'CarboPEI' chemotherapy, patients in complete remission (CR) were consolidated with 24 Gy WVRT. Between 2/2012 and 7/2018, 194 patients from 8 European countries with histologically-confirmed fully-staged localised germinoma were registered, of whom 167 were protocol pts. CR after chemotherapy was achieved in 65 patients, Of the 102 patients not in CR after chemotherapy 91 had partial remission (PR), 8 stable disease (SD), 3 progressive disease (PD). All 65 patients in CR received 24 Gy WVRT alone; two of these relapsed, both locally, 7 and 12 months after diagnosis. Of the 102 non-CR patients after chemotherapy, 91 with PR and 8 with SD received 24 Gy WVRT and 16 Gy boost, of which five relapsed (four local, one distant) 2 -7 years from diagnosis. One additional patient who remained in CR died of infection in CR, 4 years after Dx. In three patients with PD all received 24 Gy ventricular irradiation with varying tumour boosts. 16-30 Gy, no relapses occurred. Median follow-up of the whole group was 4, 2 years. 4- years event-free survival (EFS) for patients in CR treated with WVRT only (n=65) was 97% (standard error 2%). 4-years EFS for patients with non-CR ( WVRT 24 Gy and 16 Gy to 30 Gy tumour boost) (n=102) was 95% (standard error 2%). Localised germinoma in CR after chemotherapy had an excellent outcome with 24 Gy WVRT alone. 24 Gy WVRT is therefore considered the standard consolidation treatment in this group and should be used as the standard for further treatment studies in localised germinoma evaluating the recent international consensus on radiological response criteria ( Lancet Oncology accepted).